Meningitis Diagnosed With Computed Tomography Scan of Brain - Angelica Agnesia Rening; Aulia Okti Wulandari; Bherline Novita Wijaya; Destiya Ulfah Riany; Fiorentina Elitasari; Ignatius Jonathan; Ni luh Putu Trisanti; Veren Antonie; Mathias Rusli (Medical Clinical Update, 2022)
Meningitis is defined as inflammation of the meninges, which consists of dura mater, arachnoid mater, and pia mater. Meningitis can be caused by infectious and non-infectious processes such as autoimmune disorders, cancer, drug reactions. Meningitis can have a varied clinical presentation. Symptoms such as fever, neck pain or stiffness, photophobia, headache, dizziness, confusion, delirium, irritability, and nausea or vomiting may present. Signs of increased intracranial pressure such as altered mental status, neurologic deficits, and seizures indicate poor prognosis. Meningitis is diagnosed through cerebrospinal fluid analysis. However, there is controversy that the lumbar puncture could lead to brain herniation in the presence of increased intracranial pressure. Thus, Computed Tomography Scan (CT scan) could be alternative modality. In this case, we present meningitis diagnosed with CT scan of brain.